2013
DOI: 10.4209/aaqr.2013.02.0060
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Black Carbon Measurements at Two Urban Locations in New York

Abstract: Measurements of PM 2.5 black carbon (BC) over an 8-9 year period are used to characterize temporal patterns at sites in New York City (NYC) and Rochester, NY. Annual mean BC at the NYC location ranges from 1.4 to 2.0 μg/m 3 , whereas mean concentrations at Rochester are approximately a factor of 2-3 lower. BC amounts to 15-20% of PM 2.5 mass in NYC compared to 7-10% at Rochester. Seasonal patterns reveal the highest BC concentrations in NYC from November to February versus June to November at Rochester. At bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…S10, with higher concentrations (more than a factor of 2 between winter and summer) during colder months consistent with the major sources being residential heating oil combustion used for space and water heating (Lippmann, 2009). In addition the ratio of Ni to Co of around 12-14 (Rattigan et al, 2013) is typical of fuel oils used in the Northeastern states (Graham, 2010). The very low Ni concentrations observed at sites outside NYC is due to the predominant use of natural gas and wood rather than oil for domestic heating in these areas.…”
Section: (Iii) Selected Elementsmentioning
confidence: 99%
“…S10, with higher concentrations (more than a factor of 2 between winter and summer) during colder months consistent with the major sources being residential heating oil combustion used for space and water heating (Lippmann, 2009). In addition the ratio of Ni to Co of around 12-14 (Rattigan et al, 2013) is typical of fuel oils used in the Northeastern states (Graham, 2010). The very low Ni concentrations observed at sites outside NYC is due to the predominant use of natural gas and wood rather than oil for domestic heating in these areas.…”
Section: (Iii) Selected Elementsmentioning
confidence: 99%
“…10(a). Rattigan et al (2013) showed that residential wood smoke events can be observed at Rochester, especially on cold weekend nights. During this period nighttime wind speeds were generally low, and overnight minimum temperatures were near or below 0°C.…”
Section: Case Studies At Both Sitesmentioning
confidence: 99%
“…In general, elevated RGM and PBM at Rochester are associated with north/northwest winds, which may be indicative of nearby sources in those directions. The area in the immediate vicinity of the Rochester site is generally residential, and emissions from wood combustion for recreational use occasionally impact the monitoring site (e.g., Rattigan et al, 2013). …”
Section: Conditional Probability Function Analysismentioning
confidence: 99%
“…In addition the daily estimates of Delta-C were very low with an overall mean of-0.16 ± 0.17 (Table 2). C 2 O 4 2-and Delta-C are strong markers for bio-mass burning as the major source of air particulate emissions Wang et al, 2012;Rattigan et al, 2013). Thus, bio-mass burning was ruled out as a possible source of PM 2.5 in Rabigh during our study period since the estimates on C 2 O 4 2-and Delta-C were very low.…”
Section: Sources Of Rabigh Pm 25 -Positive Matrix Factorization (Pmf)mentioning
confidence: 99%
“…As shown in Eq. (1), the difference between the BC measurement at λ = 370 nm and λ = 880 nm gives the estimate for Delta-C which is a strong marker for organic matter combustion as a source of PM 2.5 Wang et al, 2012;Rattigan et al, 2013).…”
Section: Analysis Of Black Carbon (Bc)mentioning
confidence: 99%